2022
DOI: 10.3390/biom12040550
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Gallstone Formation: A Review of the Literature

Abstract: Gallstone disease is a common pathology of the digestive system with nearly a 10–20% incidence rate among adults. The mainstay of treatment is cholecystectomy, which is commonly associated with physical pain and may also seriously affect a patient’s quality of life. Clinical research suggests that cholelithiasis is closely related to the age, gender, body mass index, and other basic physical characteristics of patients. Clinical research further suggests that the occurrence of cholelithiasis is related to obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 103 publications
1
32
0
3
Order By: Relevance
“…Thirdly, from a basic pathophysiological perspective, in gallstone patients, Abcg5/g8 may be elevated expression by the role of gut microbiota or genetic variation ( 18 20 ). As mentioned above, abnormally elevated expression of Abcg5/g8 can reduce cholesterol concentration in blood by transporting more cholesterol to the intestine and bile ( 21 ). At the same time, Niemann–Pick C1-Like Protein1, a transmembrane protein highly expressed in the intestinal tract in gallstone patients, could reduce the intestinal cholesterol uptake ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, from a basic pathophysiological perspective, in gallstone patients, Abcg5/g8 may be elevated expression by the role of gut microbiota or genetic variation ( 18 20 ). As mentioned above, abnormally elevated expression of Abcg5/g8 can reduce cholesterol concentration in blood by transporting more cholesterol to the intestine and bile ( 21 ). At the same time, Niemann–Pick C1-Like Protein1, a transmembrane protein highly expressed in the intestinal tract in gallstone patients, could reduce the intestinal cholesterol uptake ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lithogenic genes 1 and 2 ( Lith1 and Lith2 ), playing a role in liver cholesterol secretion and regulating bile flow, have been described in murine models. Their human counterparts are ABCG5 and ABCG8 [ 17 ]. A recent study of 214 children with cholelithiasis showed the presence of the lithogenic ABCG8 allele p.D19H in 14.9% of children, which was more frequently reported compared to children and adults without gallstones.…”
Section: Reviewmentioning
confidence: 99%
“…Members of the Organic Anion Transporting Polypeptide (OATP) family are responsible for the uptake of unconjugated or sulfated bile acids. Enterohepatic circulation provides approximately 95% of bile acid return [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these two mechanisms, there are other factors that contribute to the formation of cholesterol gallstones, such as genetic factors and gallbladder dyskinesia[ 49 ]. Indigenous populations in North and South America are reported to be at highest risk of gallstones in the world.…”
Section: Genetic Susceptibility To Cholesterol Gallstonesmentioning
confidence: 99%